Analysis of nursing students' obsessive and coping behaviors during the COVID-19 pandemic - Bahcecioglu Turan, Gulcan; Kose, Semra; Aksoy, Meyreme (Wiley, 2021)
Purpose: This study was conducted to examine the obsessive behaviors and coping behaviors of nursing students during the coronavirus disease 2019 (COVID-19) pandemic. Design and Methods: This descriptive study was conducted between October 4 and October 17, 2020. Findings: In this study, it was found that nursing students had a mean total COVID-19 Obsessive Compulsive Scale score of 3.88 +/- 3.02 and a mean total Ways of Coping Inventory (WCI) score of 47.05 +/- 11.68. When the subscales of the WCI were examined, mean scores were found to be 13.64 +/- 4.85 for the self-confident approach, 8.91 +/- 3.35 for the optimistic approach, 7.25 +/- 2.24 for the seeking social support approach, 10.97 +/- 4.43 for the helpless approach, and 6.24 +/- 3.20 for the submissive approach. Practice Implications: Nursing students have low levels of obsession with COVID-19 and moderate levels of coping behaviors. For this reason, it is very important to recognize the psychological symptoms of today's nursing students-the health workforce of the future-and to determine priorities for their solution.
Keywords: coping behaviors; COVID-19; nursing students; obsessive behavior